2016
DOI: 10.1007/s00438-016-1174-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, classification, and analysis of NADP-ME family members from 12 crucifer species

Abstract: NADP-dependent malic enzymes (NADP-MEs) play essential roles in both normal development and stress responses in plants. Here, genome-wide analysis was performed to identify 65 putative NADP-ME genes from 12 crucifer species. These NADP-ME genes were grouped into five categories of syntenic orthologous genes and were divided into three clades of a phylogenic tree. Promoter motif analysis showed that NADP-ME1 genes in Group IV were more conserved with each other than the other NADP-ME genes in Groups I and II. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…There are many cis-acting elements related to salt stress response on DsME1P and DsME2P such as ABRE. Meanwhile, ABRE was also found in the promoter of ME in other plants . Under salt stress, ABA can regulate downstream gene expression by binding with ABRE on the promoter in plants. , However, a unique MYB binding site (MBS) was identified on DsME2P, which was not present on DsME1P.…”
Section: Discussionmentioning
confidence: 99%
“…There are many cis-acting elements related to salt stress response on DsME1P and DsME2P such as ABRE. Meanwhile, ABRE was also found in the promoter of ME in other plants . Under salt stress, ABA can regulate downstream gene expression by binding with ABRE on the promoter in plants. , However, a unique MYB binding site (MBS) was identified on DsME2P, which was not present on DsME1P.…”
Section: Discussionmentioning
confidence: 99%
“…The encoding NADP-MEs share a high degree of identity with other plant NADP-MEs, and they have distinctive domains [ 45 ]. Furthermore, the four CaNADP-MEs identified in fruits were predicted to be located in the cytosol (CaNADP-ME2) and in the plastids (CaNADP-ME3 to CaNADP-ME3 5), which is analogous to other plant species [ 9 , 47 , 59 , 60 ]. Thus, the model plant Arabidopsis contains four NADP-ME genes in its genome, and three encode for cytosolic isozymes (NADP-ME1 to NADP-ME3), whereas NADP-ME2 is located in plastids [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…LOC_Os03g15050 encodes a transaldolase, which plays an important role in glycolysis and the pentose phosphate pathway (PPP) (Caillau and Paul Quick 2005 ). In addition, LOC_Os02g44550 (an NADP-dependent malic enzyme) and LOC_Os07g42440 (a glycolate oxidase) have important functions in photosynthesis (Cui et al 2016 ; Tao et al 2016 ). It was recently found that splicing factors participated in flower and embryo development in Arabidopsis (Xiong et al 2019a , b ), and seed development in maize (Fouquet et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%